Effects of Inclisiran on Systemic Inflammatory Biomarkers: A Systematic Review - Warham Warham; Nurul Fitriani Andi Padri; Wiking Zeth; Annisa Istiqamah Ahmad; Asdwiyenti Miftahulresty Aksi; Azhim Asshiddiq Suhardi Andi Ara (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Inclisiran is a novel small interfering RNA (siRNA) therapy that specifically targets proprotein convertase subtilisin/kexin type 9 (PCSK9), thereby introducing an innovative method for the regulation of lipid levels. The implications of this intervention regarding systemic inflammatory biomarkers necessitate comprehensive investigation. Objective: To thoroughly evaluate how inclisiran influences inflammatory markers, especially high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α), among a group of people identified with hypercholesterolemia or atherosclerotic cardiovascular disease. Methods: A thorough systematic literature review was performed in accordance with the PRISMA 2020 guidelines. A meticulous search was undertaken across three databases (Scopus, ScienceDirect, PubMed) encompassing the timeframe from January 2017 to December 2025. Two independent reviewers engaged in the processes of filtering, extracting information, and quality evaluation by using the Cochrane RoB 2.0 tool, specifically crafted for randomized controlled trials (RCTs). Results: Out of an initial cohort of 304 records, 11 studies met the predetermined inclusion criteria, encompassing 4 noteworthy phase 2-3 randomized controlled trials (RCTs) (ORION-1, -9, -10, -11). Inclisiran revealed considerable reductions in LDL-C concentrations (varying from 47.9% to 52.6%), while demonstrating neutral effects on hs-CRP levels, which encompassed non-significant increases when compared to placebo (for example, from 3.5% to 8.5%). No investigations have provided data pertaining to IL-6 or TNF-α. All RCTs evaluated demonstrated a significantly low propensity for bias. Conclusions: Current empirical research indicates that inclisiran does not significantly influence systemic hs-CRP levels and lacks comprehensive data regarding other essential inflammatory biomarkers. The enhancements noted in cardiovascular wellness tied to this medication seem to be chiefly dictated by major declines in LDL-C concentrations, instead of variations in overall inflammation. Upcoming research on heart health results must incorporate a wide selection of inflammatory indicators to fully explain the complicated impacts of inclisiran.